2022
DOI: 10.3390/antiox11102026
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenol-Rich Extract from Muscadine Grapes Prevents Hypertension-Induced Diastolic Dysfunction and Oxidative Stress

Abstract: Muscadine grapes are abundant in dietary polyphenols, but their effect on hypertension-induced cardiac damage is limited. This study assessed whether a muscadine grape skin/seed extract supplement (MGES) prevents hypertension-induced cardiac damage and oxidative stress. Male Sprague Dawley rats were treated for four weeks with drinking water, angiotensin II (Ang II) to induce hypertension, MGES, or both Ang II and MGES. Cardiac function assessed by echocardiography showed that Ang II increased systolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Wiesmann et al reported that AngII-induced elevated systolic blood pressure results in impaired CBF and a decreased response to blood pressure lowering treatment in a mouse model for Alzheimer's disease [41][42]. As we known, endothelial dysfunction is associated with the oxidative stress in hypertension pathology [43][44][45][46]. Amounts of antioxidant scavengers, such as SOD, GPx, catalase and vitamin E, are decreased in patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Wiesmann et al reported that AngII-induced elevated systolic blood pressure results in impaired CBF and a decreased response to blood pressure lowering treatment in a mouse model for Alzheimer's disease [41][42]. As we known, endothelial dysfunction is associated with the oxidative stress in hypertension pathology [43][44][45][46]. Amounts of antioxidant scavengers, such as SOD, GPx, catalase and vitamin E, are decreased in patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to tobacco smoke was carried out for six weeks. Treatment with HL (administered by subcutaneous injection, analogously to angiotensin II administration in other studies [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]) started from the third week of exposure to tobacco smoke and lasted four weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Administering 5 mg HL/kg body weight per day would result in the basal concentration (10 pM) in the whole rat body after about four hours following injection, assuming a 10 min half-life of HL because of the subcutaneous route (in contrast to intravenous injection) and the average rat tissue water content of 65.6% [ 88 ]. Although the chosen dosage may seem relatively low, angiotensin II is administered to rats usually subcutaneously in the concentration range of 0.1–1.5 mg/kg body weight per day, with biological effects observed on the level of the whole organism [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Therefore, our choice for dosage is higher than that of angiotensin II (calculating it, one should also consider the difference in molecular weights of these peptides, which means that we administered from 14- to 190-fold higher molar content of HL than angiotensin II administered in other studies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation